РЕГИОНАЛЬНЫЕ КОНФЛИКТЫ НА ПОСТСОВЕТСКОМ ПРОСТРАНСТВЕ (МЕЖДУНАРОДНО-ПРАВОВОЙ АНАЛИЗ) - КАРАЕВ, Рауф Мамед оглы (SUPREMANCE OF LAW, 2016)
The article presents a comparative legal analysis of the regional conflicts in the post-Soviet space. From the standpoint of international law, the author points to the inadequacy of references to the so-called Kosovo ««precedent» in the analysis of regional conflicts in the post-Soviet space. The reasons and legal grounds for the emergence of the Kosovo problem and the regional conflicts in the former Soviet Union, are fundamentally different from each other and should be regulated by different legal norms and principles.